2017
DOI: 10.1080/21691401.2017.1374281
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of anticancer activity by silibinin and paclitaxel combination on the ovarian cancer

Abstract: Our results showed that combination of chemotherapy drugs of silibinin and paclitaxel can be more efficient in treatment of ovarian cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…In addition, silibinin is also found to display various biological activities including anti-oxidative, anti-proliferative, anti-bacterial, anti-fungal, neuro-protective, anti-leishmanial, anti-osteoclastic and anti-metastatic activities [310][311][312][313][314][315][316][317]. Previous studies have reported that silibinin exerts remarkable effects in numerous cancers such as renal, hepatocellular and pancreatic carcinoma, bladder, breast, colorectal, ovarian, lung, salivary gland, prostate and gastric cancers, through the induction of apoptosis, inhibition of tumor growth, metastasis and angiogenesis [318][319][320][321][322][323][324][325][326][327][328].…”
Section: Silibininmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, silibinin is also found to display various biological activities including anti-oxidative, anti-proliferative, anti-bacterial, anti-fungal, neuro-protective, anti-leishmanial, anti-osteoclastic and anti-metastatic activities [310][311][312][313][314][315][316][317]. Previous studies have reported that silibinin exerts remarkable effects in numerous cancers such as renal, hepatocellular and pancreatic carcinoma, bladder, breast, colorectal, ovarian, lung, salivary gland, prostate and gastric cancers, through the induction of apoptosis, inhibition of tumor growth, metastasis and angiogenesis [318][319][320][321][322][323][324][325][326][327][328].…”
Section: Silibininmentioning
confidence: 99%
“…The combination of silibinin and other drugs are used in cancer treatment to enhance the efficacy of anti-cancer effects [324,[357][358][359]. The combination of curcumin and silibinin enhances the inhibition of cell growth and reduction in telomerase gene expression compared to silibinin alone in human breast cancer T47D cells [357].…”
Section: Silibininmentioning
confidence: 99%
“…There is (40%) overexpression of genes in this pathway that is associated with BRCA1 or BRCA2 mutations and BRCA1 methylation; 2-Mutations of TP53 (96%); 3-The Rb pathway dysfunction occurs in 67% of highgrade OCs (Network, 2011;Romero & Bast, 2012). Ovarian Carcinogenesis was created by the interference of 90% P53, up to 40% p21 (WAF-1), up to 90% cyclin D1 and up to 70% cyclin B1 (Bast, Hennessy, & Mills, 2009;Landen, Birrer, & Sood, 2008;Pashaei-Asl et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…P53 mutation is an initial occurrence in ovarian cancer cells. This event is intensely related to high-grade ovarian neoplasms (Pashaei-Asl et al, 2018;Skomedal et al, 1997). P21 (CIP1/WAF1) or CDKN1A (cyclin-dependent kinase inhibitor 1A) gene is located on chromosome 6p21.2 in humans (Harper, Adami, Wei, Keyomarsi, & Elledge, 1993;Xiong et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Combinations of traditional Chinese medicines have been widely used to treat various diseases, including cancer [33][34][35][36]. The main advantages of this approach are the ability to reduce the dose and toxicity of the individual compounds, and to minimize or delay the induction of drug resistance [30].…”
Section: Discussionmentioning
confidence: 99%